2017
DOI: 10.1111/jne.12463
|View full text |Cite
|
Sign up to set email alerts
|

Acute ghrelin changes food preference from a high‐fat diet to chow during binge‐like eating in rodents

Abstract: Ghrelin, an orexigenic hormone released from the empty stomach, provides a gutbrain signal that promotes many appetitive behaviours, including anticipatory and goaldirected behaviours for palatable treats high in sugar and/or fat. In the present study, we aimed to determine whether ghrelin is able to influence and/or may even have a role in binge-like eating behaviour in rodents. Accordingly, we used a palatable scheduled feeding (PSF) paradigm in which ad lib. chow-fed rodents are trained to 'binge' on a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
(57 reference statements)
3
17
1
1
Order By: Relevance
“…Given that the mice used in our experiments were satiated, our results are in accordance with studies showing that ghrelin does not increase palatable food intake in ad libitum fed mice, but it does so in fasted mice (Alen et al 2013). This is corroborated by our previous data presenting that ghrelin does not increase peanut butter intake in satiated mice (Kalafateli et al 2017) and that its administration in rats scheduled for palatable feeding decreases high-fat-diet consumption and enhances normal chow intake (Schéle et al 2016;Bake, Hellgren, & Dickson 2017). It is therefore possible that the amylinergic mechanisms regulating food reward do not coincide with the ones mediating substance reinforcement.…”
Section: Discussionsupporting
confidence: 91%
“…Given that the mice used in our experiments were satiated, our results are in accordance with studies showing that ghrelin does not increase palatable food intake in ad libitum fed mice, but it does so in fasted mice (Alen et al 2013). This is corroborated by our previous data presenting that ghrelin does not increase peanut butter intake in satiated mice (Kalafateli et al 2017) and that its administration in rats scheduled for palatable feeding decreases high-fat-diet consumption and enhances normal chow intake (Schéle et al 2016;Bake, Hellgren, & Dickson 2017). It is therefore possible that the amylinergic mechanisms regulating food reward do not coincide with the ones mediating substance reinforcement.…”
Section: Discussionsupporting
confidence: 91%
“…For example, a recent study found that i.c.v.-injected ghrelin shifts diet preference, increasing RC intake and reducing HF intake, in rats exposed to a 2-week binge eating protocol with simultaneous access to both diets. 58 Also, it was shown that rats intermittently and time-limited fed with different palatable diets for several weeks displayed higher plasma ghrelin levels before each binge eating event. [59][60][61][62][63] In particular, one study found that increments of plasma ghrelin levels positively correlated with food anticipatory activity and that a GHSR antagonist decreased such behaviour, 60 whereas another study showed that blockade of plasma ghrelin increments attenuated the magnitude of binge-like HF intake.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, GHSR signalling may play different roles in animals exposed to binge eating protocols for longer periods of time, when changes in body weight become evident. For example, a recent study found that i.c.v.‐injected ghrelin shifts diet preference, increasing RC intake and reducing HF intake, in rats exposed to a 2‐week binge eating protocol with simultaneous access to both diets . Also, it was shown that rats intermittently and time‐limited fed with different palatable diets for several weeks displayed higher plasma ghrelin levels before each binge eating event .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the involvement of ghrelin in food reward and food motivation for palatable food, it is interesting that, when a food choice consisting of chow, lard and sucrose pellets is offered, acute delivery of ghrelin mainly induces a preference change towards chow . Moreover, in a scheduled‐feeding paradigm, when animals are bingeing on a high‐fat diet, acute delivery of ghrelin can change the food preference during the binge from a high‐fat diet to chow . Such work inspired the present study, which investigates whether ghrelin is also able to increase the motivation for healthier (less palatable) foods such as chow, even in satiated rats.…”
Section: Introductionmentioning
confidence: 95%